PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA DAN KOMPETENSI TERHADAP KINERJA GURU (STUDI PADA SEKOLAH BINA INSAN MANDIRI JAKARTA BARAT) - Aris Munandar; Nur Aini; Maswanto Maswanto (Taksasila Edukasi Insani, 2023)
ABSTRACTThis study aims to determine the effect of organizational culture, work motivation and competence on teacher performance (at Mandiri insan schools, West Jakarta). The population in this study were all teachers at SMP and SMK Bina Insan Mandiri, totaling 75 people and all of them were used as samples. The research sample was determined using the Saturated Sample technique. Data collection was carried out by distributing questionnaires using a Likert scale. The analytical method used is multiple linear analysis method. From this study it shows that the estimated multiple linear regression model is feasible to use to explain the influence of organizational culture, work motivation and competency variables on teacher performance. Simultan organizational culture and competence have a significant effect on teacher performance while work motivation has no effect on teacher performance.Keywords:Organizational culture, work motivation and competence, teacher performance